Development of Digital Flashcards to Improve Fraction Counting Skills of Students of SDN 11 Kurao Pagang - Muntazia, Azhidah; Pratiwi, Rahmi; Novrianti, Novrianti; Kurnia, Reni (Jurnal Ilmiah Mandala Education (JIME), 2025)
This research aims to develop digital flashcard media to enhance the fraction calculation skills of fifth-grade elementary school students. The development method used is Research and Development (R&D) following the 3D development model (Define, Design, Develop). The data collection instruments used include documentation, assessment formats, and questionnaires. The techniques used for data collection in this research involve material validity questionnaires, media validity questionnaires, and student practicality questionnaires. Based on the assessment results from the material validators, the material validation score was obtained at 99.28%, categorized as 'Very Valid', while the media validation score from the media validators was 89.68%, also categorized as 'Very Valid'. After the media was declared valid and feasible, it was tested on 47 fifth-grade elementary school students, achieving a practicality score of 99.78%, categorized as 'Very Practical'. These assessments indicate that the digital flashcard media is suitable for the learning process to enhance students' fraction calculation skills.